T TEKNOLOGI PENYANGRAI BIJI KOPI DENGAN ALAT UKUR MASSA SISTEM DIGITAL BERBASIS MIKROKONTROLER ARDUINO - Surya Palas; Sailon, Sailon; Ahmad Zamheri (MACHINERY Jurnal Teknologi Terapan, 2024)
Roasting coffee is a crucial process to produce high-quality coffee beans. However, the coffee roasting process is still often done manually. To address this issue, an automatic coffee roasting machine has been designed using various components such as Arduino Mega as the main controller, MLX 90614 sensor to measure temperature, load cell sensor to track the weight of coffee beans, DC motor as the coffee bean agitator, and LPG as the heating source for the roasting chamber. The research has shown that the coffee roasting machine functions well. Testing of the machine indicates that the heating temperature inside the roasting chamber can reach 150Â°C in an average time of 6.52 minutes. The load cell sensor has an accuracy rate of 99.5%, while the temperature sensor has an accuracy rate of 98.6%. With this automatic coffee roasting machine, it is expected to improve the efficiency of coffee roasting on a household scale. The machine allows for better temperature control and stable agitation, thereby helping to enhance the quality and production efficiency of coffee